PENGARUH MODEL TEAMS GAMES TOURNAMENT TERHADAP KETERAMPILAN PENGAMBILAN KEPUTUSAN DALAM PEMBELAJARAN IPS DI SEKOLAH DASAR - Septiyan, Galih Dani (Mimbar Sekolah Dasar, 2017)
This research is about the influence of application of Teams Games Tournament (TGT) type cooperative model in elementary school to decision-making skill. The research method is quasi experiment with non randomized pretest-posttes control group design. The population of all grade III elementary school in Maja subdistrict and its sampling sampling in this research is student of class III SDN Cieurih I and SDN Kertabasuki II. The purpose of this study is to determine the effect of TGT model on student decision-making skills in class III elementary school. The result of this research can be concluded that there is a difference of decision-making skills improvement between experimental and control group, besides cooperative learning of TGT is better than conventional learning in improving student decision-making skills in elementary school social study learning and there is difference of improvement of decision making skill among student group higher, middle and lower achiever using TGT model and conventional learning. Keywords: TGT type cooperative model, decision-making skill.